Deliberation analysis in participatory governance of regional development planning meeting (Musrenbang) of Barru Regency - Aenun Rijal Alwiah (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to analyze Participatory Governance in Village Development Planning (Musrenbangdes) of Pao Pao Village, Tanete Rilau District, Barru Regency which includes Deliberation, Action, Monitoring, Centralized Coordination and Power, School of Democracy and Outcomes. This study uses a qualitative method with a case study design. The case is the development planning meeting (Musrembang) in Barru Regency. Research data collection was carried out by observation, interview and document study methods. Data were analyzed using several steps according to the theory of Miles, Huberman and Saldana (2014), namely analyzing data in three steps: data condensation, presenting data, and drawing conclusions or verification. Data condensation refers to the process of selecting, narrowing, simplifying, summarizing, and transforming data. The 2022 Barru Regency RKPD Musrenbang in the Regency which is also called the Kecamatan Musrenbang is a stakeholder Deliberation Forum to discuss and agree on steps for handling priority program activities listed in the list of proposed Village/Kelurahan development activity plans that are integrated with the regional development priorities of Barru Regency in district area. The stages of the deliberation aspect are expressed by the stages of decision-making and the ideas of stakeholders as the main ideas in the decision-making process. This process must properly be tested as a fair assessment, based on public issues that need to be resolved in the sense that decisions are really important to the public. society is not a thing that benefits a handful of parties.